Multiculturalism in Malaysia and Singapore: Contesting models - Noor, Noraini M.; Leong, Chan-Hoong (Elsevier journal, 2013)
Malaysia and Singapore are good examples of multicultural societies albeit with different acculturation ideologies. Both countries comprise three main ethnic groups but in diametrically opposite proportion. In Malaysia, 50.4% of the population is Malay, 23.7% Chinese, 11%indigenous peoples, 7.1% Indian, and 7.8% other races. In Singapore, the ratio is 74.1% Chinese, 13.4% Malay, 9.2% Indian and 3.3% other races. Due to its colonial past, “ethnicity” has been the central policy issue in Malaysia and remains so up to this day. The dominance of communal politics can be understood in Stephan and Stephan’s (2000) model of integrated threat theory. In Singapore, the city-state does not believe in affirmative action and it prefers to manage cultural identities on the basis of a multicultural ideology (Berry & Kalin,1995; Berry, Kalin, & Taylor, 1977). In this article, multiculturalism is used to refer to public policies carried out by the two countries to manage their plural societies. We will discuss the development of the multicultural models that have evolved in the two countries. While Malaysia’s model of multiculturalism is based on policies that have been instituted to manage inter-group tensions, prevent violence, and pursue social justice between the ethnic groups as a result of its past, Singapore’s model is guided by pragmatic realism and market fundamentals associated with the needs of a global city. Both models will face challenges in the coming years as they each adapt to the seismic shifts in the geo-economic landscapes.